AN ANALYSIS ON THE ELEMENTARY SCHOOL TEACHERS’ ABILITY IN IMPLEMENTING THEMATIC APPROACH - Rizki Ananda; Fadhilaturrahmi Fadhilaturrahmi (Universitas Negeri Medan, 2018)
Abstract: An Analysis on The Elementary School Teachers’ Ability in Implementing Thematic Approach. The Regulation of Minister National of Education Republic of Indonesia Number 40 Year 2007 states the implementation of thematic approach in the teaching and learning process at the elementary school level. Dealing with the implementation of Curriculum 2013, the implementation of thematic approach could not be hindered. The teachers have to implement the thematic approach as the professional career. This research was aimed at: 1) analyzing the teachers’ understanding on the thematic approach, 2) capturing the teachers’ practice in implementing thematic approach, and 3) gaining information on the teachers’ difficulties in implementing thematic approach. The study was a descriptive qualitative. The subject of the research was the 1st up to the 3rd grade elementary school teachers of the three elementary schools at Bangkinang Kota. The data were gathered by interview and observation technique. Triangulation was done through Forum Group Discussion among the researchers, the teachers, and the headmasters. The findings of the research were classified into conceptual and practical. Conceptually, the teachers have a good understanding on the thematic approach, but practically were not at all. 6 of 9 teachers have been implemented thematic approach in the learning and teaching process. The teachers were also met the difficulties in implementing the approach.Keywords: the ability of teachers, elementary school teachers, thematic approach.Abstrak: Analisis Kemampuan Guru Sekolah Dasar Dalam Implementasi Pembelajaran Tematik. Peraturan Menteri Pendidikan Nasional Nomor 41 tahun 2007 mengisyaratkan penggunaan pendekatan tematik dalam pembelajaran kelas 1 sampai kelas 3 Sekolah Dasar (SD). Bahkan dewasa ini pasca diberlakukannya Kurikulum 2013, pendekatan tematik wajib diimplementasikan dari kelas 1 sampai kelas 6 pada proses pembelajaran. Adalah menjadi hal yang penting bagi guru SD untuk dapat melaksanakan pendekatan tematik sebagai tanggung jawab profesi. Penelitian ini bertujuan untuk: 1) menganalisis pemahaman guru SD tentang pendekatan tematik, 2) mendapatkan profil kemampuan guru SD dalam melaksanakan pendekatan tematik, dan 3) mengetahui hambatan-hambatan guru dalam mengimplementasikan pendekatan tematik di SD. Penelitian menggunakan metode deskriptif kualitatif dengan subjek penelitian guru kelas 1 sampai kelas 3 di tiga SD Kecamatan Bangkinang Kota. Data dikumpulkan dengan observasi dan wawancara. Triangulasi dilakukan melalui fokus grup discussion antara peneliti, guru, dan kepala sekolah. Hasil penelitian menunjukkan bahwa secara konsep guru memahami pendekatan tematik dengan baik, namun pada pelaksanaannya 6 dari 9 orang guru yang diteliti tidak melaksanakan pendekatan tematik dalam pembelajaran. Penelitian ini juga mengungkapkan bahwa sebagian besar guru mengalami kendala dalam mengimplementasikan pendekatan tematik pada proses pembelajaran.Kata Kunci: kemampuan guru, guru Sekolah Dasar, pendekatan tematik